Tobin tax proposal : background, issues and prospects - Felix, David (UNDP New YorkUS, 1994)
Argues that a Tobin tax is probably superior on various counts, including technical feasibility to alternative proposals that have been floated, however, getting it formally into the policy arena presents problems. Elaborates on the tax proposal by responding to questions and issues submitted by the HDRO.